Detecting the shape of anisotropic gold nanoparticles in dispersion with single particle extinction and scattering. Issue 8 (3rd February 2017) - Potenza, M. A. C.; Krpetić, Ž.; Sanvito, T.; Cai, Q.; Monopoli, M.; de Araújo, J. M.; Cella, C.; Boselli, L.; Castagnola, V.; Milani, P.; Dawson, K. A.
Abstract : Single particle extinction and scattering (SPES) is used to detect the shape of anisotropic gold nanoparticles in dispersion in situ. Abstract : The shape and size of nanoparticles are important parameters affecting their biodistribution, bioactivity, and toxicity. The high-throughput characterisation of the nanoparticle shape in dispersion is a fundamental prerequisite for realistic in vitro and in vivo evaluation, however, with routinely available bench-top optical characterisation techniques, it remains a challenging task. Herein, we demonstrate the efficacy of a single particle extinction and scattering (SPES) technique for the in situ detection of the shape of nanoparticles in dispersion, applied to a small library of anisotropic gold particles, with a potential development for in-line detection. The use of SPES paves the way to the routine quantitative analysis of nanoparticles dispersed in biologically relevant fluids, which is of importance for the nanosafety assessment and any in vitro and in vivo administration of nanomaterials.